2017
DOI: 10.1007/978-94-024-1141-6_6
|View full text |Cite
|
Sign up to set email alerts
|

Intergenerational Relationships in Migrant Families. Theoretical and Methodological Issues

Abstract: Migration has become a family based project, whether it involves the migration of the whole family, the formation of family post-migration or the financial support of family in the country of origin. The growing tendency of migrants to settle permanently rather than to practice circular migrations raises new challenges, not only for migration policy but also for integration patterns and for family policy and practices. We are convinced that a generational approach is one of the most inspiring ways to explore s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Current research shows that intergenerational parent-child relations in immigrant families are very complex and have several domains. Attias-Donfut and Cook (2017) reviewed the current scholarship covering five key topics: the contraction of nuclear family relations; the central positions taken by the children; the changes in gender relations; the transmission of patterns of behavior; and intergenerational social mobility. Many empirical studies show how migration conditions parenthood and vice versa.…”
Section: Conceptual Background: Parent-child Relationships In the Posmentioning
confidence: 99%
See 1 more Smart Citation
“…Current research shows that intergenerational parent-child relations in immigrant families are very complex and have several domains. Attias-Donfut and Cook (2017) reviewed the current scholarship covering five key topics: the contraction of nuclear family relations; the central positions taken by the children; the changes in gender relations; the transmission of patterns of behavior; and intergenerational social mobility. Many empirical studies show how migration conditions parenthood and vice versa.…”
Section: Conceptual Background: Parent-child Relationships In the Posmentioning
confidence: 99%
“…However, as Cook and Waite (2016) argue, in the literature, "there has been too much emphasis on the divisions between "'traditional' parents and 'modern' children at the expense of examining the ways in which both generations change and adapt" Waite, 2016: 1389). Post-migratory intergenerational relationships are far more complex than those simple divisions, and the perception and experience of migration vary from one generation to another, as previous research has demonstrated (Attias-Donfut and Cook, 2017;Foner and Dreby, 2011).…”
Section: Introductionmentioning
confidence: 99%